FEATURES OF PREGNANCY AND DELIVERY CLINICAL COURSE DEPENDING ON LOCALIZATION OF PLACENTA IN THE UTERUS - Удовицька, Н.О. (World of Medicine and Biology, 2015)
The clinical course of pregnancy and childbirth in 1080 women. A ultrasound scans - in 1450 (over time); anthropometry - 560; CTG - 710 (dynamics); tonusmetry - 242; SEQ morphological studies - 80. It was established that the clinical course of delivery depending on the localization of the placenta in the uterus. Its location in the upper part of the uterus contributes to the weakness of labor. Conversely, in low-lying placenta are more common hypotonic bleeding in the postpartum period. Prediction of the weakness of labor should be carried out taking into account the identified risks. Revealed the dependence of labor on the location of the placenta in the uterus enabled obstetrician-gynecologist to take into account this factor in predicting the development of DRS. Timely forecasting and adequate prevention reduced the incidence of TSS TSS 3 times, and operative delivery - 2 times.
Keywords: pregnancy; childbirth; the placenta; uterine inertia